Pengaruh Pendapatan dan Harga Pokok Penjualan Terhadap Laba Kotor Pada PT. Agra Pura Bahari Megapolitan Sukabumi - Gunawan, Ujang (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The aims in this study is knowing the effect of the Effect and Cost of Goods Sold on Gross Profit at PT. Agra Pura Bahari Megapolitan Sukabumi. The population of this study is the financial statements of PT. Agra Pura Bahari Megapolitan. In this study, researchers used saturated sampling. Saturated sampling is a determination technique when all populations are used as samples. The independent variables are the raw material cost budget and employee performance. The data collection used is secondary data, namely sources that do not directly provide data to data collectors, for example through other people or through documents. The data collected were analyzed using multiple linear regression with hypothesis testing partial test (t) and simultaneous test (F). Based on the results of the study, it is known that the Significance value (Sig) of the Income variable (X1) is 0.007. Because the value of Sig. 0.007 < probability 0.05, it can be concluded that H1 or the first hypothesis is rejected. This means that there is an effect of Income (X1) on Gross Profit (Y). Based on the results of the discussion, it can be concluded that the independent variables, namely Income, and COGS, simultaneously or simultaneously have a significant effect on Gross Profit. Based on the calculation of the coefficient of determination, it is known that the value of Kd = 99.9%, it can be concluded that the effect of Income and COGS on Gross Profit is included in the very strong criteria.